Identifying The Influence of Social Community on Hotel Image, Halal Services, and Halal Food on the Revisit - Naldi Hendri; Yunia Wardi; Erni Masdupi (LPPM Universitas PGRI Sumatera Barat, 2022)
This study aims to systematically identify, review, and evaluate literature on the social community’s perception of hotels, halal-friendly services and staff, as well as halal food and beverages, in order to increase the intention to return among Muslim guests at Muslim-friendly hotels in Padang, West Sumatra, and to provide an agenda for future research. This study evaluates the intention to return to stay on this topic, identifies limitations and gaps in the existing literature, and proposes potential studies to expand knowledge in this field. This study uses a systematic literature review method. This study used the keywords ‘social community’, ‘hotel image’, ‘halal-friendly services and staff’, ‘halal food and beverages’, and ‘intention to return’. This study found 454 articles through a search on Science Direct using other applications such as Mendeley and VOSViewer, which were then filtered to select 56 articles for descriptive analysis. Content analysis, assisted by Microsoft Excel, was used for review and analysis purposes. The findings show that hotel image, halal-friendly services and staff, and halal food and beverages have a positive relationship with the intention to revisit and recommend. A series of product/service Offerings were then developed and tested to determine the most effective way to meet visitor expectations and increase visitor satisfaction and the intention to revisit Muslim-friendly hotels in Padang, West Sumatra, in the future